2019
DOI: 10.1142/s0217979219502138
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal synchronization in asymmetrically bidirectionally coupled neurons over a complex network

Abstract: The spatiotemporal synchronous activity of delay coupled chaotic systems in a network is very important to understand the communications through neurons of the human body. In this paper, we present a homogeneous one-dimensional delay coupled neuron model in a complex network. We design a network model in which the links are stochastically updated at every time step. In this model, the nodes of the network are bidirectionally asymmetrically coupled instead of usual symmetric coupling. We further analyze the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been reported that such time delay is a fundamental part of almost all biological phenomena in nervous systems and can improve the function of the neural network (synchronization and stability). [37][38][39] Thus, the time delay of the signal is considered in the current work.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that such time delay is a fundamental part of almost all biological phenomena in nervous systems and can improve the function of the neural network (synchronization and stability). [37][38][39] Thus, the time delay of the signal is considered in the current work.…”
Section: Introductionmentioning
confidence: 99%